Nordic Walking Training Causes a Decrease in Blood Cholesterol in Elderly Women Supplemented with Vitamin D - Prusik, Krzysztof; Kortas, Jakub; Prusik, Katarzyna; Mieszkowski, Jan; Jaworska, Joanna; Skrobot, Wojciech; Lipinski, Marcin; Ziemann, Ewa; Antosiewicz, Jedrzej (Frontiers in Endocrinology, 2018)
Objective Different studies have demonstrated that regular exercise can induce changes in the lipid profile, but results remain inconclusive. Available data suggest that correction of vitamin D deficiency can improve the lipid profile. In this study, we have hypothesized that Nordic walking training will improve lipid profile in elderly women supplemented with vitamin D. Methods The total of 109 elderly women (68 ± 5.12 years old) took part in the study. First group (Experimental:EG, 35 women) underwent 12 weeks of Nordic Walking training combined with vitamin D supplementation (4000 IU per day), second group (Supplementation: SG, 48 women) was only supplemented with vitamin D (4000 IU per day), and third group (Control: CG, 31 women) was not subject to any interventions. . Blood analysis of total cholesterol (TC), triglycerides (TG), HDL-C, LDL-C, 25-OH-D3 was performed at baseline and after the 12 weeks of Nordic Walking training. Additionally, a battery of field tests specifically developed for older adults was used to assess the components of functional fitness. The same blood analysis was repeated for the EG six months after the main experiment. Results After 12 weeks of NW training and vitamin D supplementation, in the EG a decrease in TC, LDL-C and TG was observed. In the SG, no changes in the lipid profile were observed, whereas in the CG an increase in the level of HDL was noticed. Positive physical fitness changes were only observed in the EG. Conclusion Our obtained data confirmed baseline assumption that regular exercise induce positive alternations in lipid profile in elderly women supported by supplementation of vitamin D. Key words: physical fitness, LDL, HDL, health training